The Effect of Using the Android-based “MBARENGI” E-Module Statistics on Student Learning Outcomes at the University of Muhammadiyah Sidoarjo: Pengaruh Penggunaan E-Modul Statistika “MBARENGI” berbasis Android pada Hasil Belajar Mahasiswa di Universitas Muhammadiyah Sidoarjo - Cahyaning, Cindy; Wiguna, Akbar; Latifah, Fitri Nur; Alfina, Irma Agustin Dwi (Procedia of Social Sciences and Humanities, 2022)
In teaching and learning process, educators are required to be able to create an innovation with the aim of encouraging students to be able to follow teaching and learning process well. Innovation in learning media is one type of innovation that can be done by an educator. Learning media is one components of learning that has an important role in teaching and learning activities, especially in the transition after the Covid 19 pandemic. The use of smartphones can be one of the innovations of learning media by using Android-based e-modules. This research is a development research or known as Research and Development (R&D) using the ADDIE development model (Analyze, Design, development, Implementation, and Evaluation). The Android-based “MBARENGI” statistics e-module was validated by material experts, learning media experts, and tested on a limited group. Based on the feasibility test that has been carried out on material experts and media experts, it can be concluded that the Android-based E-Module is feasible and can be implemented in the learning process. Based on the paired hypothesis testing (t-paired) the value of count (12.45) > for ttable (2.16) is obtained, the resulting decision is to reject H0 so that the interpretation of the results of the paired hypothesis testing (t-paired) is the E-Statistics Module "MBARENGI" based on Android has a statistically significant effect on student learning outcomes. The large influence test is obtained through the eta square value of 0.94 > 0.14 so it is included in the category that has a large influence. Based on the eta squared value, it can be concluded that the E-Modul Statistics "MBARENGI" learning media based on Android has a statistically significant effect on student learning outcomes with a large effect of 94%.